PERANCANGAN IKON BANGUNAN BERSEJARAH DI SURABAYA - Satrya Dirgantara (Prahasta Publisher (manage by: DRPM Institut Bisnis dan Teknologi Indonesia), 2022)
Surabaya is a large city that is developing. Although Surabaya is known as a metropolitan city, the city of Surabaya has many relics of colonial-era cultural heritage, many buildings – historic buildings of Dutch colonial heritage are still sturdy and magnificent to this day. This design raised 5 historic buildings in the city of Surabaya to be illustrated by vector. The buildings includes Tugu Pahlawan, Balai Pemuda Surabaya, Balai Kota Surabaya, De Javasche Bank, and Kantor Pos Kebonrojo. The goal is to documented this historic building in the form of an vector illustration. The vector illustration is carried out using the stages of Robin Landa’s design process which includes orientation, analysis, concepts, design, and implementation. Through this design, the historic building in Surabaya can be documented as an vector illustration.